Class Action Lawsuits in Human Rights Cases: Stigma 65 Strategies for Filed Class Action Lawsuits - Via Melati Sukma (Universitas Negeri Semarang, 2018)
Book written and edited by Restaria F. Hutabarat who was then a public lawyer for LBH in Jakarta. The book, entitled STIGMA 65 Strategies for Submitting Class Action Lawsuits, is also a historical and legal document regarding the activities of LBH Jakarta which conducted class action with victims of the 1965 stigma. This activity not only succeeded in documenting gross human rights violations after the events of the September 30th Movement (G30S) 1965 but also caused the consolidation of victims and challenged the performance of the judiciary towards the restoration of victims' rights. On the one hand, this text can serve as a guide for law enforcement officials, students, and the legal community in Indonesia, on the other hand, it is also a narrative about the history of human rights violations in the country and the struggles of victims. This book begins with the case of Nurhasyim, an errand boy at the Bogor Mayor's office who had been appointed a civil servant who had been temporarily dismissed starting November 1, 1965 because he was accused of being involved in the G30S rebellion.